Translation of english to spanish of the book “How To Teach Engljsh” by Jeremy Harmer - MASA MEDINA, MARÍA DEL CISNE (2010)
The translation of the book ‘’How to teach English’’ written by Jeremy Harmer, has the general objective to provide either people at the start of their teaching career or an initial teacher training course teaching English information as a foreign or second language. There are chapters discuss general issues about teaching and learning, help teachers to manage classes better either their physical presence or the organization the room. They are also some basic concepts of grammar, vocabulary, language use, pronunciation and punctuation. How teachers should use textbooks they should be followed or adapted to the teacher and the students’ needs. As well as, why teachers need to plan their lessons and how they can do so. Additionally, there are important suggestions how to deal with problems which teachers frequently encounter. How, if at all, can they be resolved? So, our main objective for the translation of the present book is to provide English teachers and students Teaching English information with variety of learning activities that produce a significant learning and to learn as teacher as well as a student with the purpose to improve the quality of Teaching English. Finally, we concluded that this book will be a very useful tool of reference both initial and experienced teachers so they will find all information about English Language teaching learning process. We hope that people who are involved in teaching read this book.